Injury risk and severity in a sample of Maryland residents with serious mental illness. Issue 1 (2nd June 2012) - McGinty, Emma E; Baker, Susan P; Steinwachs, Donald M; Daumit, Gail
Abstract : Objective: Adults with serious mental illness experience premature mortality and heightened risk for medical disease, but little is known about the burden of injuries in this population. The objective of this study was to describe injury incidence among persons with serious mental illness. Methods: We conducted a retrospective cohort study of 6234 Maryl and Medicaid recipients with serious mental illness from 1994–2001. Injuries were classified using the Barell Matrix. Relative risks were calculated to compare injury rates among the study cohort with injury rates in the United States population. Cox proportional hazards modeling with time dependent covariates was used to assess factors related to risk of injury and injury-related death. Results: Forty-three percent of the Maryland Medicaid cohort had any injury diagnosis. Of the 7298 injuries incurred, the most common categories were systemic injuries due to poisoning (10.4%), open wounds to the head/face (8.9%), and superficial injuries, fractures, and sprains of the extremities (8.6%, 8.5%, and 8.4%, respectively). Injury incidence was 80% higher and risk for fatal injury was more than four and a half times higher among the cohort with serious mental illness compared to the general population. Alcohol and drug abuse were associated with both risk of injury and risk of injury-related death with hazard ratios of 1.87 and 4.76 at the p<0.05 significance level, respectively. Conclusions: The superficial, minor nature of the majority of injuries is consistent with acts of minor victimization and violence or falls. High risk of fatal and non-fatal injury among this group indicates need for increased injury prevention efforts targeting persons with serious mental illness and their caregivers.